Environmentally friendly anti-corrosion treatment method for sluice gate plate after rusting
The corrosion of the slug of the slug is cleaned through dry ice refrigeration technology and high-pressure water guns, and materials such as rust converters and water-based epoxy anticorrosion primer are used to form a corrosion-resistant conversion film and corrosion-resistant layer, which solves the strength reduction and safety hazards caused by rust of the slug, and achieves a long-life environmentally friendly and anti-corrosion effect.
Patent Information
- Application Number
- CN202411952321.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to effectively prevent the strength reduction and safety hazards caused by rust caused by rust after working in the splashing area, especially when rust remains in grooves, joints and under the damaged coating that has not been cleaned.
Dry ice freezing technology and high-pressure water guns were used to clean the rust on the surface, grooves and joints of the shutter plates, and then a corrosion-resistant conversion film was used to form a corrosion-resistant conversion film, and on this basis, water-based epoxy anticorrosion primer and water-based acrylic topcoat were applied.
Effective corrosion protection on the surface, grooves and joints of the gate plate are achieved, and a dense corrosion resistance conversion film and a stable corrosion protection layer are formed, which significantly extends the service life of the gate plate and improves safety.
Smart Images

Figure BDA0005215138350000061 
Figure BDA0005215138350000071 
Figure BDA0005215138350000072
Abstract
Description
Technical Field
[0001] The invention relates to the field of gate plate anti-corrosion, and in particular to an environmentally friendly anti-corrosion technology for sluice gate plates that have been working in a splash zone for a long time and have been corroded. Background Art
[0002] The material of the sluice gate plate is steel plate. Due to long-term exposure to air and partial immersion in the splash zone of seawater, river water and lake water, it is easy to rust under the combined action of air, water and electrolyte. Although the new gate plates have been heavily anti-corrosion treated, due to the harsh environment, most of the gate plates begin to rust after a short period of use. The relevant departments must rush to carry out anti-corrosion treatment during the dry season to avoid safety hazards caused by the reduction of strength due to rust of the gate plates.
[0003] The commonly used anti-corrosion treatment at present is to clean the surface of the rusted gate plate, polish and clean the rust and damaged coating on the gate plate, and then apply anti-corrosion primer and anti-corrosion topcoat on the whole. Since the rust and damaged coating in the grooves and seams are difficult to clean, there are still rust in the grooves and seams and under the damaged coating that has not been cleaned. There are also a few firmly attached rust on the cleaned board surface. The rust removal effect does not meet the expected requirements, and there are still weak parts. After the gate plate that has been treated with anti-rust is re-entered into the water, the above-mentioned weak parts quickly begin to rust and gradually spread to the entire gate surface, resulting in anti-corrosion failure. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes an environmentally friendly anti-corrosion treatment method for rusted sluice gate plates capable of long-term anti-corrosion, comprising:
[0005] An environmentally friendly anti-corrosion treatment method for a sluice gate plate after rusting, characterized by comprising:
[0006] Step 1: Use dry ice freezing technology to freeze and destroy the rust and damaged coating on the gate surface and the grooves and seams, and use a high-pressure water gun to strongly wash the grooves, seams and surface of the gate to wash away the rust and damaged coating;
[0007] Step 2: Wait for the gate surface to dry;
[0008] Step 3: Apply rust conversion agent to the grooves, seams and the entire surface of the gate plate, and the rust conversion agent and the floating rust on the gate plate surface are converted into a corrosion-resistant conversion film, and wait for the conversion film to dry;
[0009] Step 4: Apply corrosion-resistant water-based epoxy anti-corrosion primer to the grooves, seams and the entire surface of the gate plate, and pay attention to increasing the amount of coating in the grooves and seams, and wait for the water-based epoxy anti-corrosion primer to cure;
[0010] Step 5: Apply aging-resistant water-based acrylic polyurethane topcoat or water-based acrylic ester topcoat on the surface of the cured water-based epoxy anti-corrosion primer, and pay attention to increasing the coating amount in the grooves and seams.
[0011] The technical solution adopted by an embodiment of the present invention to solve its technical problem is: the high-pressure water gun flushing pressure is 3000-4000PSI.
[0012] The technical solution adopted by an embodiment of the present invention to solve the technical problem is: the amount of the rust conversion agent in step 3 is 50 to 300 g / m2.
[0013] The raw materials of the rust conversion agent include, by weight percentage, 10-40% ethylhexyl acrylate, 1-20% methacrylic acid, 0-20% acrylic acid, 0.25-0.5% peroxide initiator, 1-3% anionic emulsifier, 0.5-1.5% nonionic emulsifier, 1-3% film-forming aid, and the balance is water.
[0014] A technical solution adopted by an embodiment of the present invention to solve the technical problem is: the anionic emulsifier is polyoxyethylene ether ammonium sulfate.
[0015] A technical solution adopted by an embodiment of the present invention to solve the technical problem is: the non-ionic emulsifier is fatty alcohol polyoxyethylene ether.
[0016] A technical solution adopted by an embodiment of the present invention to solve the technical problem is: the peroxide initiator is ammonium persulfate or potassium persulfate.
[0017] An embodiment of the present invention adopts a technical solution to solve the technical problem as follows: the preparation method of the rust conversion agent comprises:
[0018] S1. Weigh the raw materials according to the formula;
[0019] S2, dissolving the peroxide initiator in water to prepare a 10 wt % initiator solution;
[0020] S3, dissolving anionic emulsifier and nonionic emulsifier in water to prepare a 5wt% emulsifier solution, wherein the mass ratio of anionic emulsifier to nonionic emulsifier in the emulsifier solution is 2:1, retaining a small amount of emulsifier solution, adding ethylhexyl acrylate, methacrylic acid, and acrylic acid monomers into the remaining emulsifier solution and dispersing them to obtain a monomer emulsion;
[0021] S4. Add the retained emulsifier solution into the reaction container, heat it to 80-85°C, add part of the monomer emulsion and initiator solvent and stir evenly, then gradually drop the remaining monomer emulsion and initiator solution into the reaction container, stir and react at about 80°C for about 4-5h, heat it to 90-95°C, continue to react for 1-2h under vacuum conditions and then cool it down to 40-50°C, add film-forming aid, stir evenly to obtain a water-based acrylate copolymer type rust converter.
[0022] The technical solution adopted by an embodiment of the present invention to solve its technical problem is: in step 4, the amount of water-based epoxy anti-corrosion primer used is 100-200g / m2 on the board surface, and the amount used in the grooves and seams is 200-400g / m2.
[0023] The technical solution adopted by an embodiment of the present invention to solve its technical problem is: in step 5, the amount of water-based acrylic ester topcoat or water-based acrylic topcoat used is 60-150g / m2 on the board surface, and the amount used in the grooves and seams is 100-300g / m2.
[0024] Beneficial effects of the present invention: The present application uses dry ice freezing technology and a high-pressure water gun to clean the grooves, seams and surfaces of the gate plate, and then uses a rust converter to react with the floating rust on the surface of the gate plate and in the grooves and seams to generate a dense corrosion-resistant conversion film, which can be firmly attached to the surface of the gate plate. At the same time, the conversion film generated after the application of the water-based acrylic copolymer type rust converter has excellent waterproof properties and can prevent water and moisture from continuing to contact the iron substrate, thereby preventing the iron substrate from continuing to rust; then the grooves, seams and entire surface of the gate plate are coated with corrosion-resistant water-based epoxy anti-corrosion primer, aging-resistant water-based acrylic polyurethane topcoat or water-based acrylic topcoat in turn to further protect the steel substrate and the conversion film, thereby forming effective protection on the grooves, seams and surfaces of the gate plate, thereby achieving the purpose of long-life environmentally friendly anti-corrosion management. DETAILED DESCRIPTION
[0025] The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those of ordinary skill in the art. The present invention is further described in detail below in conjunction with specific examples and with reference to data. It should be understood that this embodiment is only for illustrating the present invention, and is not intended to limit the scope of the present invention in any way.
[0026] In the following examples, various processes and methods not described in detail are conventional methods known in the art. The materials, reagents, devices, instruments, equipment, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources.
[0027] The environmental protection and anti-corrosion treatment method for the sluice gate plate after rusting described in the present application includes:
[0028] Step 1: Use dry ice freezing technology to freeze and destroy the rust and damaged coating on the gate surface and the grooves and seams, and use a high-pressure water gun to strongly flush the grooves, seams and surface of the gate to rinse away the rust and damaged coating.
[0029] In step 1, the specific method of using dry ice freezing technology to freeze and destroy the rust and damaged coating on the gate surface and in the grooves and seams includes: spraying dry ice particles onto the grooves, seams and rust and damaged coating on the surface of the gate. The dry ice particles quickly reduce the surface temperature of the gate to below minus 50 degrees, causing the rust and damaged coating to crack and become brittle, destroying the connection between the rust and damaged coating and the steel surface, and generating a strong explosive force, thereby making the rust and damaged coating easy to peel off.
[0030] Use a high-pressure water gun to wash the grooves, seams and surfaces of the gate plate with force, and wash away the cracked and brittle rust and damaged coating, so as to facilitate the subsequent treatment of the gate plate with rust conversion agent;
[0031] Step 2: Wait for the gate surface to dry;
[0032] Step 3: After the gate plate surface is dry, apply rust conversion agent to the grooves, seams and the entire surface of the gate plate. The rust conversion agent reacts with the floating rust on the gate plate surface to convert into a corrosion-resistant conversion film, and wait for the conversion film to dry;
[0033] The raw materials of the rust conversion agent include, by weight percentage, 10-40% ethylhexyl acrylate, 1-20% methacrylic acid, 0-20% acrylic acid, 0.25-0.5% peroxide initiator, 1-3% anionic emulsifier, 0.5-1.5% nonionic emulsifier, 1-3% film-forming aid, and the balance is water.
[0034] The preparation method of the rust conversion agent comprises:
[0035] S1. Weigh the raw materials according to the formula;
[0036] S2, dissolving the peroxide initiator in water to prepare a 10 wt % initiator solution;
[0037] S3, dissolving anionic emulsifier and nonionic emulsifier in water to prepare a 5wt% emulsifier solution, wherein the mass ratio of anionic emulsifier to nonionic emulsifier in the emulsifier solution is 2:1, retaining a small amount of emulsifier solution, adding ethylhexyl acrylate, methacrylic acid, and acrylic acid monomers into the remaining emulsifier solution and dispersing them to obtain a monomer emulsion;
[0038] S4. Add the retained emulsifier solution into the reaction container, heat it to 80-85°C, add part of the monomer emulsion and initiator solvent and stir evenly, then gradually drop the remaining monomer emulsion and initiator solution into the reaction container, stir and react at about 80°C for about 4-5h, heat it to 90-95°C, continue to react for 1-2h under vacuum conditions and then cool it down to 40-50°C, add film-forming aid, stir evenly to obtain a water-based acrylate copolymer type rust converter.
[0039] When the rust converter is applied to the grooves, seams and the entire surface of the gate plate, the amount of the rust converter is 50 to 300 g / ㎡; examples of the raw material component content of the rust converter are shown in Table 1.
[0040] Table 1
[0041]
[0042]
[0043] The water-based acrylate copolymer rust conversion agent prepared in composition 1-3 is applied to the iron sheet with yellow rust at a dosage of 100 g / ㎡. After a period of time, a black corrosion-resistant conversion film layer is formed on the rusty iron sheet.
[0044] In this embodiment, the rusty iron sheet producing the corrosion-resistant conversion film layer of composition 1 was subjected to a neutral salt spray test according to the method of GB / T 1771-2007, and the test results are shown in Table 2; the coating adhesion test was carried out according to the standard of GB / T 9286-2021, and the test results are shown in Table 2.
[0045] Table 2
[0046]
[0047]
[0048] According to the test results in Table 2, the corrosion-resistant conversion film produced by coating the rusty iron sheet with the water-based acrylate copolymer rust converter can withstand neutral salt spray for 144 hours, and has excellent neutral salt spray resistance.
[0049] The carboxyl groups in the methacrylic acid and acrylic acid units in the water-based acrylic ester copolymer react with rust to form a dense high conversion film that can firmly adhere to the metal surface. At the same time, the conversion film formed after the application of the water-based acrylic ester copolymer type rust conversion agent has excellent waterproof properties and can prevent water and moisture from continuing to contact the iron substrate, thereby preventing the iron substrate from continuing to rust.
[0050] Methacrylic acid is used to replace part of the acrylic acid monomer to generate a copolymer. The introduced methacrylic acid unit has weaker acidity than acrylic acid due to the electron-donating property of the methyl group. After partially replacing the acrylic acid unit, the acidity of the rust converter can be reduced, which can not only solve the rust problem on the steel bars, but also avoid the corrosion of the rust converter to the concrete matrix.
[0051] Ethylhexyl acrylate monomer is introduced into the water-based acrylate copolymer type rust conversion agent. The ethylhexyl acrylate monomer has a relatively long hydrophobic side group, which can provide better hydrophobic properties for the copolymer, improve the salt spray resistance of the rust conversion film, and make the conversion film generated after the application of the water-based acrylate copolymer type rust conversion agent have a neutral salt spray resistance test result of up to 144h.
[0052] Step 4. After the coating of step 3 is completed, the floating rust on the surface of the gate plate forms a black conversion film, and the grooves, seams and the entire surface of the gate plate are painted with corrosion-resistant water-based epoxy anti-corrosion primer, and the grooves and seams are treated with enhanced treatment. The amount of water-based epoxy anti-corrosion primer is 100-200g / ㎡ on the plate surface, and the amount of grooves and seams is 200-400g / ㎡, and the water-based epoxy anti-corrosion primer is cured. In this embodiment, the water-based epoxy anti-corrosion primer is used. Water-based nano-epoxy anti-corrosion primer;
[0053] Step 5: After the waterborne epoxy anticorrosion primer is cured, an aging-resistant waterborne acrylic polyurethane topcoat or a waterborne acrylic ester topcoat is applied on the dried surface of the waterborne epoxy anticorrosion primer, and the grooves and seams are treated with enhanced treatment. The amount of the waterborne acrylic polyurethane topcoat or the waterborne acrylic ester topcoat is 60 to 150 g / ㎡ on the board surface, and 100 to 300 g / ㎡ on the grooves and seams. Water-based yellowing resistant acrylic polyurethane topcoat or The water-based acrylic topcoat eventually forms a stable, aging-resistant anti-corrosion layer on the gate surface.
[0054] Of course, the present invention is not limited to the above-mentioned embodiments, and those skilled in the art may make equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications and substitutions are all included in the scope defined by the claims of this application.
Claims
1. An environmentally friendly anti-corrosion treatment method for rusted sluice gate plates, characterized in that: include: Step 1: Use dry ice freezing technology to freeze and destroy the rust and damaged coating on the gate surface and the grooves and seams, and use a high-pressure water gun to strongly wash the grooves, seams and surface of the gate to wash away the rust and damaged coating; Step 2: Wait for the gate surface to dry; Step 3: Apply rust conversion agent to the grooves, seams and the entire surface of the gate plate, and the rust conversion agent and the floating rust on the gate plate surface are converted into a corrosion-resistant conversion film, and wait for the conversion film to dry; Step 4: Apply corrosion-resistant water-based epoxy anti-corrosion primer to the grooves, seams and the entire surface of the gate plate, and pay attention to increasing the amount of coating in the grooves and seams, and wait for the water-based epoxy anti-corrosion primer to cure; Step 5: Apply aging-resistant water-based acrylic polyurethane topcoat or water-based acrylic ester topcoat on the surface of the cured water-based epoxy anti-corrosion primer, and pay attention to increasing the coating amount in the grooves and seams.
2. The environmentally friendly anti-corrosion treatment method for rusted sluice gate plates according to claim 1, characterized in that: The high-pressure water gun flushing pressure is 3000~4000PSI.
3. The environmentally friendly anti-corrosion treatment method for rusted sluice gate plates according to claim 1, characterized in that: The amount of rust conversion agent used in step 3 is 50-300 g / ㎡.
4. The environmentally friendly anti-corrosion treatment method for rusted sluice gate plates according to claim 1, characterized in that: The raw materials of the rust conversion agent include, by weight percentage, 10-40% ethylhexyl acrylate, 1-20% methacrylic acid, 0-20% acrylic acid, 0.25-0.5% peroxide initiator, 1-3% anionic emulsifier, 0.5-1.5% nonionic emulsifier, 1-3% film-forming aid, and the balance is water.
5. The environmentally friendly anti-corrosion treatment method for rusted sluice gate plates according to claim 4, characterized in that: The anionic emulsifier is polyoxyethylene ether ammonium sulfate.
6. The comprehensive treatment method for building concrete reinforcement corrosion according to claim 4 is characterized in that: The nonionic emulsifier is fatty alcohol polyoxyethylene ether.
7. The environmentally friendly anti-corrosion treatment method for rusted sluice gate plates according to claim 4, characterized in that: The peroxide initiator is ammonium persulfate or potassium persulfate.
8. The environmentally friendly anti-corrosion treatment method for rusted sluice gate plates according to claim 1, characterized in that: The preparation method of the rust conversion agent comprises: S1. Weigh the raw materials according to the formula; S2, dissolving the peroxide initiator in water to prepare a 10 wt % initiator solution; S3, dissolving anionic emulsifier and nonionic emulsifier in water to prepare a 5wt% emulsifier solution, wherein the mass ratio of anionic emulsifier to nonionic emulsifier in the emulsifier solution is 2:1, retaining a small amount of emulsifier solution, adding ethylhexyl acrylate, methacrylic acid, and acrylic acid monomers into the remaining emulsifier solution and dispersing them to obtain a monomer emulsion; S4. Add the retained emulsifier solution into the reaction container, heat it to 80-85°C, add part of the monomer emulsion and initiator solvent and stir evenly, then gradually drop the remaining monomer emulsion and initiator solution into the reaction container, stir and react at about 80°C for about 4-5h, heat it to 90-95°C, continue to react for 1-2h under vacuum conditions and then cool it down to 40-50°C, add film-forming aid, stir evenly to obtain a water-based acrylate copolymer type rust converter.
9. The environmentally friendly anti-corrosion treatment method for rusted sluice gate plates according to claim 1, characterized in that: In step 4, the amount of water-based epoxy anti-corrosion primer used is 100-200g / ㎡ on the board surface, and 200-400g / ㎡ on the grooves and seams.
10. The environmentally friendly anti-corrosion treatment method for rusted sluice gate plates according to claim 1, characterized in that: In step 5, the amount of water-based acrylic topcoat or water-based acrylic topcoat used is 60-150g / ㎡ on the board surface, and 100-300g / ㎡ in the grooves and seams.